SOME ANGER METAPHORS IN SPANISH AND ENGLISH. A CONTRASTIVE REVIEW - Soriano, Cristina (International Journal of English Studies, 2003)
In spite of being very similar, the metaphorical models of anger in English and Spanish exhibit some differences too. These have been analyzed along a number of parameters: existence of the mapping in the language, degree of conceptual elaboration, degree of linguistic conventionalization and degree of linguistic exploitation. A number of examples evidencing cross-linguistic differences at these four levels will be presented. We will conclude with a brief discussion of the possible motivation of these differences and some observations on the study of conceptual metaphor in general.